A Proposal for a Modern Curriculum for the Arabic Language Syntax and Morphology: مقترحٌ لمنهجٍ حديثٍ لنحوِ اللغةِ العربيةِ وصرفِها واشتقاقِها - Al-Balushi, Rashid (Journal of Arabic Language Learning and Teaching (JALLT), 2025)
This paper presents a proposal for a modern curriculum for Arabic that includes answers to questions related to its syntax, inflection, and derivation. To introduce the proposal, the paper discusses a problem related to theoretical linguistic research conducted on Arabic, which is that most of these studies aim only to refine the linguistic theories and improve the theoretical frameworks, rather than serving the Arabic language. This paper, therefore, presents a proposal related to the future investigations of Arabic within modern theoretical frameworks, to be implemented within a cultural scheme or an intellectual initiative that utilizes the efforts, knowledge, and interests of the Arab scholars and students of Arabic for the purpose of finding new answers to various questions related to the constructions and properties of Arabic. The paper then provides examples of the linguistic questions and cultural issues that may be investigated using the modern linguistic theories and frameworks, so that new answers may be reached. The paper illustrates the advantages of such a program in terms of enhancing the interests of the new generations in investigating Arabic and studying it using the effective methods, as well as developing the students’ analysis, critical thinking, and problem-solving abilities at all stages.